Thyroid Function and Dysfunction in Relation to 16 Cardiovascular Diseases: A Mendelian Randomization Study. (March 2019) - Larsson, Susanna C.; Allara, Elias; Mason, Amy M.; Michaëlsson, Karl; Burgess, Stephen
Abstract : Background: Subclinical thyroid dysfunction, defined as thyroid-stimulating hormone levels outside the reference range with normal free thyroxine levels in asymptomatic patients, is associated with alterations in cardiac hemodynamics. We used Mendelian randomization to assess the role of thyroid dysfunction for cardiovascular disease (CVD). Methods: Single-nucleotide polymorphisms associated with thyroid function were identified from a genome-wide association meta-analysis in up to 72 167 individuals. Data for genetic associations with CVD were obtained from meta-analyses of genome-wide association studies of atrial fibrillation (n=537 409 individuals), coronary artery disease (n=184 305 individuals), and ischemic stroke (n=438 847) as well as from the UK Biobank (n=367 703 individuals). Results: Genetically predicted thyroid-stimulating hormone levels and hyperthyroidism were statistically significantly associated with atrial fibrillation but no other CVDs at the Bonferroni-corrected level of significance ( P <7.8×10 −4 ). The odds ratios of atrial fibrillation were 1.15 (95% CI, 1.11–1.19; P =2.4×10 −14 ) per genetically predicted 1 SD decrease in thyroid-stimulating hormone levels and 1.05 (95% CI, 1.03–1.08; P =5.4×10 −5 ) for genetic predisposition to hyperthyroidism. Genetically predicted free thyroxin levels were not statistically significantly associated with any CVD. Conclusions: This Mendelian randomization study supports evidence for a causal association of decreased thyroid-stimulating hormone levels in the direction of a mild form of hyperthyroidism with an increased risk of atrial fibrillation but no other CVDs. Abstract : Supplemental Digital Content is available in the text.